Real-Time Cartoon Shaded Smoke Rendered with Transparency and Silhouette - Lemos, Cássio Fehlberg; Maciel, Anderson; Torchelsen, Rafael Piccin (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais da XXXVI Conference on Graphics, Patterns and Images, 2023)
This paper presents a method for real-time rendering of toon-shaded smoke stylized with silhouettes. The proposed method aims to achieve visually appealing smoke effects that are compatible with the toon shading style commonly used in animated movies and games. The technique involves modeling smoke particles as small geometries, allowing for better illu-mination and control over the shading steps. Transparency is computed using a geometry-sorting method, which facilitates the efficient rendering of overlapping particles without sacrificing performance. Silhouette detection is employed to create smooth, consistent silhouettes around the smoke, enhancing the visual quality of the effect. The implementation utilizes WebGL and Three.js, and performance tests demonstrate its feasibility on modest hardware configurations for wide use in games. The results show that the presented approach offers real-time performance and artistic compatibility with toon shading, opening up new possibilities for creating stylized smoke effects in interactive applications.